A mixed analytical-numerical method for the acoustic radiation of a spherical double shell in the ocean-acoustic environment. (1st March 2020) - Zou, Ming-Song; Liu, Shu-Xiao; Jiang, Ling-Wen; Huang, He
Abstract: This study presents a mixed analytical-numerical method based on the analytical method and the wave superposition method to predict the acoustic radiation of a spherical double shell immersed in the ocean-acoustic environment. Using the Green's function, the fluid structure coupled vibration as well as the near and far field acoustic radiations can be simultaneously analyzed. Different forms of Green's functions are utilized to deal with the near and far field distribution of sound pressure. To reduce the complexity of the computation, the image-source method is used in the near field while the normal mode method is adopted in the far field. The acoustic radiation fields of the spherical double shell in finite depth ocean-acoustic environment with positive and negative gradient sound speed profiles are calculated using the proposed method. Numerical results compared with results using the finite element method obtained by COMSOL verify that the proposed method improves the computational efficiency without losing computational accuracy. Further, taking the spherical double shell as an example, the effects of seabed, sea surface, and sound speed profile of seawater on the fluid structure coupled vibration, acoustic radiation, and sound propagation of underwater structures are analyzed. Some figures are also included to show these effects clearly. The main idea proposed in this paper can be applied to the integrated calculation of fluid structure coupled vibration and the near and far field acoustic radiations of arbitrary three-dimensional elastic floating bodies in the ocean-acoustic environment. Graphical abstract: Image 1 Highlights: The near and far fields are regarded as a unified system. Acoustic radiation field is presented considering complicated sound speed profiles. The proposed method can give reliable results for a large water domain. The presented results could serve as a benchmark for the pure numerical method.